Implementasi Manajemen dalam Pembelajaran Sejarah di Sekolah Menengah Atas - Niara, Kautsar; Nugraha, Muhammad Andika; Agustina, Ema (Universitas Negeri Gorontalo, 2026)
This study aims to formulate an adaptive and systematic history learning management matrix to bridge the gap between curriculum regulations and the reality of conventional classroom practices. The study employs a literature synthesis approach, analyzing contemporary research findings including the implementation of Project-Based Learning (PjBL), Problem-Based Learning (PBL), Contextual Teaching and Learning (CTL), and the management of controversial historical issues. Findings indicate that the effectiveness of history learning depends not only on pedagogical models but also on the strength of operational management. Based on an analysis of modern management theories and innovative field practices, this research reconstructs the POAC (Planning, Organizing, Actuating, Controlling) framework into a practical guidance matrix for educators. The integrated POAC matrix transforms the teacher's role into an effective learning manager capable of managing digital resources, navigating complex historical narratives, and increasing active student engagement. This model offers an implementable solution for creating a critical, contextual, and reflective history learning ecosystem